Advancing sustainable water-energy solutions through a hybrid photovoltaic-thermal stepped solar still - Krish Hemantkumar Gandhi; Mihir Ashwinkumar Kelawala; Rajesh S; Chiranjeevi Chalasani (Energy Nexus, 2025)
The dual challenges of freshwater scarcity and increasing energy demand have intensified interest in sustainable, integrated solar desalination systems. Conventional solar stills (CSS) often exhibit low thermal efficiency and limited freshwater output, making them unsuitable for large-scale use. To address these limitations, this study presents a multidimensional advancement in sustainable water–energy systems through the development of a novel Photovoltaic-Thermal Stepped Solar Still (PVT-SSS) integrated with a bilateral serpentine flow design. The objective is to enhance thermal performance, increase freshwater production, and recover energy more efficiently from solar input. A dynamic, climate-responsive simulation model was developed using mass and energy balance equations, solved with a fourth-order Runge–Kutta (RK4) method to predict real-time thermal behavior under varying environmental conditions. A three-dimensional spatial optimization analysis was conducted to identify the optimal collector area(Ac)and saline water mass flow rate (mw)˙, enabling location-specific design scalability and improved operational efficiency. To evaluate the influence of mass flow rate on system performance, experiments were conducted at 0.3, 0.5, 0.75, and 1.0 LPM flow rates. At 0.3 LPM, the system achieved an annual freshwater yield of 1262.9 L/m²/year, showing improvements of 16.5 %, 40.65 %, and 77.43 % over those recorded at 0.5, 0.75, and 1.0 LPM. Experimental validation recorded a peak electrical output of 118.22 W, with electrical efficiency (ηel) ranging from 8.55 %–9.4 %, and thermal efficiency (ηth)ranging from 15 % to 35 %. Compared to existing systems, the proposed PVT-SSS system showed an average improvement of 26.23 % in thermal efficiency, 60.33 % in electrical efficiency, and 56.45 % in freshwater yield. The cost per liter (CPL) was $0.07, reflecting a 43.91 % reduction compared to other hybrid systems. Additionally, an enviroeconomic analysis was carried out at varying flow rates to assess the system's long-term viability. Overall, the PVT-SSS system demonstrates a scalable, energy-efficient, and environmentally friendly solution aligned with Sustainable Development Goals (SDGs) 6 and 7.